2014
DOI: 10.1016/j.fob.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Conditional targeting of Ispd using paired Cas9 nickase and a single DNA template in mice

Abstract: HighlightsWe generated a floxed allele by using paired Cas9n (nickase), gRNAs and single DNA template in mouse.We confirmed that the floxed allele was germline transmitted and functional in F1 offspring.A floxed allele of the isoprenoid synthase containing domain (Ispd) gene in C57BL/6N background mice was created.This method can be used to generate knockout mice for genes that are potentially embryonic lethal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…There are three previous studies reporting the generation of conditional mutant mice by introduction of two flox sites using the CRISPR/Cas9 system101112. However, no reported studies have used the one-step CRISPR/Cas9 system to generate floxed mice and subsequently tissue-specific knockout mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three previous studies reporting the generation of conditional mutant mice by introduction of two flox sites using the CRISPR/Cas9 system101112. However, no reported studies have used the one-step CRISPR/Cas9 system to generate floxed mice and subsequently tissue-specific knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…Because the binding of Cas9 is guided by simple base-pair complementarities between engineered single-guide RNA (sgRNA) and target genomic DNA sequences, it is possible to direct Cas9 to any genomic locus by providing engineered sgRNA. Previous reports have demonstrated that the generation of floxed mice in one step by the insertion of two loxP sites into the same allele of genes using the CRISPR/Cas9 system101112. However, the generation of tissue-specific knockout (KO) mice by crossing floxed mice developed using the methods outlined above with tissue-specific Cre Tg mice has yet to reported.…”
mentioning
confidence: 99%
“…Nevertheless, there are reports of DSD templates injected into the mouse zygote for the integration of reporter transgenes 70, 71 or a conditional allele. 72 These studies utilized conventional homology arms of variable lengths (3–9 kb) in a circular DSD template; linearization of the DSD donor is not done so as to reduce random integration in the mouse genome. Recently, DSD templates with shorter homology arms (0.3 kb) were used in mouse ESC to generate a reporter mouse line.…”
Section: Components Of Crispr Genome Editingmentioning
confidence: 99%
“…One method combines a sgRNA with Cas9n and a double-strand DNA donor template carrying both loxP sites. 72 A second method involves the synthesis of two SSO of length no more than 180 nucleotides with the 34 base pair loxP sequence placed at the center of the SSO within 10 base pairs of the DSB (Supplemental Figure IV). This approach is essentially identical to one previously published.…”
Section: Three Component Crisprmentioning
confidence: 99%
“…This has now been demonstrated both in cell lines and in murine models. 65,66 Again, CRISPR/Cas provides an advantage compared with ZFNs and TALENs here, because the flexibility of sgRNA-dependent targeting increases the likelihood that any particular mutation can be introduced. One of the most established methods for generating an allelic series in mammalian cells via HDR is that which uses adeno-associated virus (AAV).…”
Section: Crispr/cas and Other Editing Technologiesmentioning
confidence: 99%